Classification of granitic relief in the territory of the Sertão Monumental Geopark Project, Brazil - Alexandre Pinheiro Alcântara; Vanda Claudino-Sales; João Luis Sampaio Olímpio; Adriano Luís Heck Simon; Rubson Pinheiro Maia (Investigaciones Geográficas)
The granitic relief is notable in the Brazilian northeastern landscape due to its resistance to geomorphological processes. In the territory of the Sertão Monumental Geopark Project, which covers the Ceará municipalities of Quixadá and Quixeramobim, there is a significant occurrence of the granitic features, with different shapes and sizes showing subsurface and surface processes. The Etchplanation Theory and morphodynamic studies enabled the analysis of the development of these forms, which was conducted through a literature review, fieldwork and photographic records. The features were classified into macroforms and microforms, taking into account their characteristics and origin. Macroforms are extensive plutonic bodies that stand out in areas of planation relief, exhibiting diverse morphogenetic characteristics, with varying sizes, including inselgebirg, inselberg, flagstones and vertical outcrops. The microforms were subdivided into features associated with weathering, saprolitization and fracturing, and include tafoni, “honeycomb”, karren, gnammas and flared slopes. This classification and hierarchization contributes to future research and further study on the subject of granitic relief.